2019
DOI: 10.1007/s40629-018-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hymenoptera venom allergy and sensitization in the population-representative German KORA cohort

Abstract: Purpose Allergic reactions to Hymenoptera venoms represent potentially life-threatening conditions. However, studies on their prevalence in Germany and their relation to specific IgE sensitization are rare. The aim of this study was to evaluate the prevalence of Hymenoptera venom allergy as well as the frequency of venom-specific IgE sensitization in a large population-based adult German cohort. Methods Questionnaire data were collected from the participants of the German population-based KORA S. Blank and S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…As sIgE sensitization rates depend on various factors, the definition of minor and major allergens is difficult in many cases and should perhaps be handled flexible, depending on the assessed patient popula-review tion and the methods used. Additionally, sIgE sensitization per se implies no information about its clinical relevance [22] and the ability of allergens to activate effector cells [23].…”
Section: Sensitization Rates To Marker Allergens Of Hymenoptera Venomsmentioning
confidence: 99%
“…As sIgE sensitization rates depend on various factors, the definition of minor and major allergens is difficult in many cases and should perhaps be handled flexible, depending on the assessed patient popula-review tion and the methods used. Additionally, sIgE sensitization per se implies no information about its clinical relevance [22] and the ability of allergens to activate effector cells [23].…”
Section: Sensitization Rates To Marker Allergens Of Hymenoptera Venomsmentioning
confidence: 99%
“…• 3. High t-IgE levels may influence the rate of sensitization to bee and wasp venoms [13,19]. Indeed, none of the 22 subjects in our study with a t-IgE <50 IU/l showed sIgE to Hymenoptera venoms whereas 24 of 31 (77.4%) with a t-IgE >250 IU/l had sIgE to Hymenoptera venoms.…”
Section: Plos Onementioning
confidence: 58%
“…Interestingly, the presence of sIgE does not necessarily imply clinically relevant venom allergy. Between 9% and 29% of the population are sensitized to Hymenoptera venoms without previous clinical history of a sting reaction (39,40). For most of these patients it is likely that the sensitization is asymptomatic and, thus, of no clinical relevance (41).…”
Section: Asymptomatic Sensitizationmentioning
confidence: 99%
“…The verification of a previous SR by clinical history should build the basis for a subsequent diagnostic work-up ( Figure 3) since asymptomatic sensitization to Hymenoptera venoms is observed frequently (39,40). A thorough clinical history includes information on number and date of sting reactions, symptoms, severity and time course of the reaction as well as the applied treatment.…”
Section: Clinical Historymentioning
confidence: 99%
See 1 more Smart Citation